Genome-Wide Characterization of the Fur Regulatory Network Reveals a Link between Catechol Degradation and Bacillibactin Metabolism in Bacillus subtilis - Hualiang Pi (American Society for Microbiology, 2018)
ABSTRACT The ferric uptake regulator (Fur) is the global iron biosensor in many bacteria. Fur functions as an iron-dependent transcriptional repressor for most of its regulated genes. There are a few examples where holo-Fur activates transcription, either directly or indirectly. Recent studies suggest that apo-Fur might also act as a positive regulator and that, besides iron metabolism, the Fur regulon might encompass other biological processes such as DNA synthesis, energy metabolism, and biofilm formation. Here, we obtained a genomic view of the Fur regulatory network in Bacillus subtilis using chromatin immunoprecipitation sequencing (ChIP-seq). Besides the known Fur target sites, 70 putative DNA binding sites were identified, and the vast majority had higher occupancy under iron-sufficient conditions. Among the new sites detected, a Fur binding site in the promoter region of the catDE operon is of particular interest. This operon, encoding catechol 2,3-dioxygenase, is critical for catechol degradation and is under negative regulation of CatR and YodB. These three repressors (Fur, CatR, and YodB) function cooperatively to regulate the transcription of catDE, with Fur functioning as a sensor of iron limitation and CatR as the major sensor of catechol stress. Genetic analysis suggests that CatDE is involved in metabolism of the catecholate siderophore bacillibactin, particularly when bacillibactin is constitutively produced and accumulates intracellularly, potentially generating endogenous toxic catechol derivatives. This study documents a role for catechol degradation in bacillibactin metabolism and provides evidence that catechol 2,3-dioxygenase can detoxify endogenously produced catechol substrates in addition to its more widely studied role in biodegradation of environmental aromatic compounds and pollutants. IMPORTANCE Many bacteria synthesize high-affinity iron chelators (siderophores). Siderophore-mediated iron acquisition is an efficient and widely utilized strategy for bacteria to meet their cellular iron requirements. One prominent class of siderophores uses catecholate groups to chelate iron. B. subtilis bacillibactin, structurally similar to enterobactin (made by enteric bacteria), is a triscatecholate siderophore that is hydrolyzed to monomeric units after import to release iron. However, the ultimate fates of these catechol compounds and their potential toxicities have not been defined previously. We performed genome-wide identification of Fur binding sites in vivo and uncovered a connection between catechol degradation and bacillibactin metabolism in B. subtilis. Besides its role in the detoxification of environmental catechols, the catechol 2,3-dioxygenase encoded by catDE also protects cells from intoxication by endogenous bacillibactin-derived catechol metabolites under iron-limited conditions. These findings shed light on the degradation pathway and precursor recycling of the catecholate siderophores.